Features of Ultrastructural Changes in Colonic Mucosa in Experimental Modeling of Adjuvant Arthritis - N.N Kaladze; T.G. Filonenko; O.A. Sizova (Zaslavsky O.Yu., 2013)
The experiment proved the inclusion of compensatory reactions manifested by an increase in the number of functionally active goblet cells, aimed to restorarion of colonic mucosal barrier.